Effective teaching strategies: lessons from research and practice - Killen, Roy (Social Science Press, Thomson Katoomba, 2005)
"Third edition guide to teaching strategies. This edition includes revised material and three introductory chapters that discuss a theoretical base for teaching, outcomes-based education, and teacher reflection. Looks at direct instruction, discussion, small-group work, co-operative learning, problem solving, student research, role-play, case studies and student writing. Includes questions, exercises, appendices, references and subject index." - product description